VIRTUAL SCREENING APPROACH OF DRUG DESIGNING FOR PARKINSON’S DISEASE - KULDEEP SAHU; DR. SATPAL SINGH BISHT (International Journal of Pharma and Bio Sciences, 2013)
Parkinson’s disease PARK1, caused by mutations in the SNCA gene, which codes for the protein alpha-synuclein. SNCA gene is analysed by different NCBI tools and bioinformatics softwares (ORF, Map Viewer, e-PCR, Vec screen, Genscan, BLAST, FASTA, MSA, ClustalW, bioedit software and phylodraw software). Then protein information and protein structures are analysed by different proteomics tools and different softwares (Protparam, Protscale, GOR, SOPMA, SignalP, NetNGly, NetOGly, NetAcet, NetPhos, sulfinator, SOSUI, bioedit software, SPDBV software, RASMOL 3D analysis software). Homology modelling of the protein is done using SPDBV (SWISS PDB VIEWER). Active site analysis is done through Q-site finder method and the active site amino acids are noted. Standard available market drugs targeting the protein were identified as Carbidopa, Dopamine, Levodopa, Memantine, and Apomorphine. 16 similar molecules for these standard molecules were modelled using Argus Lab software. A database is created with all these molecules in Vega ZZ software. Virtual screening of these drugs is done through protein-database docking method. QSAR analysis is done through Hyperchem software. UV & IR transitions are done through CAche software.